Determinants of Health Protocols Compliance on Office Workers - Mufiedah, Liena Asma' 'Abiedatul; Karyani, Usmi; Hertinjung, Wisnu Sri (Universitas Muhammadiyah Surakarta, 2023)
Abstract. The high number of Covid-19 cases contributed to office clusters. To reduce the spread of Covid-19, the government has implemented the 5M health protocol. However many people, especially office workers, violate this health protocol. One of the available approaches to analyze non-compliance behavior is by using the Health Belief Model (HBM). This study aims to determine the factors affecting office workers' compliance with the Covid-19 preventive health protocol, explained bythe Health BeliefModel (HBM) theory to develop health promotion programs which may contribute to the compliance level of the office workers. This research is a correlational quantitative study with a sample of 357 office workers in the Surakarta residency. The data were collected online by usings six scales uploaded in the Google Form, consisting of the perceived susceptibility scale, perceived severity scale, perceived barriers scale, perceived benefits scale, self-efficacy scale, and the Covid-19 prevention protocol compliance scale. The path analysis was carried out by using JASP 14.1 to analyze the collected data. The result shows that health protocols are greatly helped for workers by many cues/stimuli that will appear with the many perceived barriers in implementing health protocols but will increase with relevant facts. Self-efficacy plays a vital role in influencing health protocol compliance in office workers. Providing more intense education that focuses on providing solutions that workers can take when facing difficulties in implementing health protocols can be one way to further increase confidence in workers in implementing health protocols.Keywords: compliance; health belief model; health protocol; office worker